A scoping review of longitudinal studies of athlete burnout - Dišlere, Beate Evelīna; Mārtinsone, Kristīne; Koļesņikova, Jeļena (Frontiers in Psychology, 2025)
IntroductionPrior research has shown that increasing training and competition loads, along with associated stressors, can negatively impact athletes’ mental health and contribute to burnout. While athlete burnout can be associated with various negative sports-related consequences, such as withdrawal from sports or injuries. Although most studies on athlete burnout employ cross-sectional designs, longitudinal approaches could provide valuable insights into athlete burnout changes over time and potential causal relationships between variables and burnout. Therefore, this study aims to systematically examine longitudinal design studies to offer a comprehensive methodological, conceptual, and practical overview of athlete burnout and its associated factors.MethodsFollowing PRISMA-ScR guidelines, this review explores what factors influence changes in burnout levels among athletes throughout a sports season. Therefore, studies were selected that examined athlete burnout across both genders, all age groups, and various sport types, using repeated measurements. Published articles from 2014 to 2024 were collected. Eligible studies were identified through three databases: PubMed, Scopus, and Web of Science.ResultsA total of 32 studies were analyzed. Quantitative mapping highlights study demographics, measurement approaches, and procedures, while qualitative mapping identifies 26 factors categorized as risk, protective, and factors influenced by burnout. The review highlights the use of tools like the Athlete Burnout Questionnaire and identifies optimal data collection intervals for tracking burnout dynamics.ConclusionThis scoping review offers insights into the multidimensional and nonlinear nature of athlete burnout, emphasizing its development through longitudinal studies and the importance of monitoring specific dimensions. The findings revealed various athlete burnout influencing personal and sport-environmental factors, including risk factors like perfectionistic concerns and negative social interaction, protective factors such as resilience-related skills and relatedness, and social support. The study emphasizes the importance of early detection and longitudinal monitoring to prevent burnout and mitigate its impact on athletes’ mental health and performance. Further research is needed to explore additional risk and protective factors to develop effective interventions aimed at reducing the risk of burnout in athletes.